Pitfalls and suggestions for the treatment of open, comminuted fractures of the middle phalanx using custom-made dynamic external fixators: a retrospective case series. Issue 6 (30th November 2022) - Ntourantonis, Dimitrios; Iliopoulos, Ilias; Pantazis, Konstantinos; Baikousis, Andreas; Korovessis, Panagiotis
Abstract : Background: The proximal interphalangeal joint (PIPJ) is a synovial joint prone to injury encompassing a wide spectrum of severity. In the setting of complicated injuries, dynamic external traction systems are considered to be the optimal treatment modality with numerous different Kirschner-wire configurations combined with rubber bands, springs, pulleys, or hinges being described. However, many of these pose significant technical challenges for the surgeon or are unwieldy to the patient emphasizing the need for simple, easy to construct, and well-tolerated modifications, which are equally effective in reducing the fracture and allowing early motion. Methods: The authors retrospectively analyzed prospectively collected data of 12 patients with open complex PIPJ fracture dislocations treated with a custom-made external fixator based on the one that was originally suggested by Suzuki et al . All patients were men with an average age of 55.1 yr (23 to 81). Injured digits involved four index, five middle, and three ring fingers. Results: The mean follow-up was 54.36 mo, and all patients healed without a second operation and returned to their jobs and preinjury level of activity. The average active range of motion of the PIPJ was 75.16±3.18 degrees, DIPJ was 69.33±14.7 degrees, and MCPJ was 88.75±1.97 degrees. Mean Quick Disabilities of Arm, Shoulder, and Hand (DASH)-Japan Society for Surgery of the Hand (JSSH) score at the final examination was 4.33±1.38 (range 2.3 to 6.8). The authors recorded five complications involving two rubber bands breaking, one pin-track infection, one rubber band-axial traction pin malposition, and one swan neck deformity, which were treated accordingly. Conclusions: One of the most crucial factors affecting outcome in this kind of injury is the appearance of the digit and functional results. None of the participants in this series had any complaint about the appearance of their fingers in the final examination, and 10 out of 12 judged the cosmetic result as very good. To the authors' knowledge, this report is one of the few that describes the functional outcome of pins and rubbers traction system (PRTS) application in complex fracture and fractures-dislocations with severe comminution of the middle phalanx and not only fractures related to the PIP joint. Level of Evidence: Level V.